Oak tree-rings record spatial-temporal pollution trends from different sources in Terni (Central Italy). (February 2018) - Perone, A.; Cocozza, C.; Cherubini, P.; Bachmann, O.; Guillong, M.; Lasserre, B.; Marchetti, M.; Tognetti, R.
Abstract: Monitoring atmospheric pollution in industrial areas near urban center is essential to infer past levels of contamination and to evaluate the impact for environmental health and safety. The main aim of this study was to understand if the chemical composition of tree-ring wood can be used for monitoring spatial-temporal variability of pollutants in Terni, Central Italy, one of the most polluted towns in Italy. Tree cores were taken from 32 downy oaks ( Quercus pubescens ) located at different distances from several pollutant sources, including a large steel factory. Trace element (Cr, Co, Cu, Pb, Hg, Mo, Ni, Tl, W, U, V, and Zn) index in tree-ring wood was determined using high-resolution laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). We hypothesized that the presence of contaminants detected in tree-rings reflected industrial activities over time. The accumulation of contaminants in tree-rings was affected by anthropogenic activities in the period 1958–2009, though signals varied in intensity with the distance of trees from the industrial plant. A stronger limitation of tree growth was observed in the proximity of the industrial plant in comparison with other pollutant sources. Levels of Cr, Ni, Mo, V, U and W increased in tree-ring profiles of trees close to the steel factory, especially during the 80's and 90's, in correspondence to a peak of pollution in this period, as recorded by air quality monitoring stations. Uranium contents in our tree-rings were difficult to explain, while the higher contents of Cu, Hg, Pb, and Tl could be related to the contaminants released from an incinerator located close to the industrial plant. The accumulation of contaminants in tree-rings reflected the historical variation of environmental pollution in the considered urban context. Graphical abstract: Image 1 Highlights: Contaminants detected in tree-rings reflected industrial activities over time. Environmental signals varied with the distance of trees from the industrial plant. A strong limitation of trees growth was observed in trees near industrial plant. LA-ICP-MS analysis was successfully used in detecting trace elements in tree-rings. Abstract : Pollution legacy in cities can be reconstructed through the analysis of urban trees.